1988
DOI: 10.1111/j.1432-1033.1988.tb14083.x
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory nitrate reductase from Paracoccus denitrificans

Abstract: 1. The b-type haem centres of the three (a, fi and y) subunit nitrate reductase from Paracoccus denitrijkans have been analysed by redox potentiometry. Two components were identified with mid-point potentials + 95 mV and +210 mV.2. Washing, in the absence of Mg2+ ions, of cytoplasmic membrane vesicles from P. denitriJicans promoted selective release of nitrate reductase activity. The released enzyme was purified by chromatography and shown to contain a and fi, but not y polypeptides. A haem spectrum was absent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 25 publications
(10 reference statements)
6
32
0
Order By: Relevance
“…We have previously shown that the BV . ϩ :NO 3 Ϫ oxidoreductase activity appears to be independent of the presence of NarI (2,24). This prompted us to investigate whether the NarI-H56R mutation has any effect on the assembly or conformation of the NarH [Fe-S] clusters.…”
Section: Fig 3 Redox Titration Of Narghi-enriched Membranesmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the BV . ϩ :NO 3 Ϫ oxidoreductase activity appears to be independent of the presence of NarI (2,24). This prompted us to investigate whether the NarI-H56R mutation has any effect on the assembly or conformation of the NarH [Fe-S] clusters.…”
Section: Fig 3 Redox Titration Of Narghi-enriched Membranesmentioning
confidence: 99%
“…3 Comparison of the potentiometric titration data from the wild-type enzyme (Fig. 3) with the effect of the H56R mutation on the heme EPR line shape (Fig.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The first reduction step in the process of denitrification is catalyzed by nitrate reductase (Nar), which converts nitrate to nitrite: NO~-+ 2H + + 2e----> NO~-+ HzO. This membrane-bound enzyme resembles the dissimilatory nitrate reductase of E. coil to a great extent (Ballard and Ferguson, 1988;Stewart, 1988). The enzyme consists of three different subunits (a, 13, and "y) and it is suggested that during nitrate reduction electrons from ubiquinol are passed to the b-type heroes in the -,/-subunit and subsequently via iron-sulfur centers in the 13-subunit to the molybdenum cofactor, which is located in the a-subunit (Fig.…”
Section: The Anaerobic Respiratory Networkmentioning
confidence: 99%
“…With the exception of the eukaryotic nitrate reductases, which are part of the sulfite oxidase family, all the prokaryotic nitrate reductases belong to the dimethyl sulfoxide (DMSO) reductase family of Mo-containing enzymes [7]. The respiratory nitrate reduction pathway involves the membrane-bound respiratory nitrate reductase (Nar), which has been isolated from a variety of organisms, including a few well-studied bacteria [8][9][10][11][12][13][14]. Nars are involved in the redox loop generating the proton motive force across biomembranes [15].…”
Section: Introductionmentioning
confidence: 99%